A combined field analysis and modeling approach for assessing the impact of groundwater pumping on streamflow - Flores, Luke, author; Bailey, Ryan T., advisor; Gates, Timothy K., committee member; Sanford, William E., committee member (Colorado State University. Libraries, 2018)
The magnitude of volumetric water exchange between streams and alluvial aquifers impacts contaminant transport rates, channel erosion and sedimentation, nutrient loading, and aquatic and riparian habitat. Quantifying the interactions between stream water and groundwater is also critically important in regions where surface water and tributary groundwater are jointly administered under a prior appropriation doctrine, such as in the western United States. Of particular concern is the effect of a nearby pumping well on streamflow. When the cone of influence of a pumping well reaches a nearby stream, the resulting hydraulic gradient can induce enhanced seepage of streamflow into the aquifer or decrease the rate of groundwater discharge to the stream. The change in these rates is often modeled using analytical or numerical solutions, or some combination of both. Analytical solutions, although simple to apply, can produce discrepancies between field data and model output due to assumptions regarding stream and aquifer geometry and homogeneity of hydraulic parameters. Furthermore, the accuracy of such models has not been investigated in detail due to the difficulty in measuring streamflow loss in the field. In the first part of this thesis, a field experiment was conducted along a reach of the South Platte River in Denver, Colorado to estimate pumping-induced streamflow loss and groundwater head drawdown, and compare data against analytical modeling results. The analytical solutions proved accurate if streamflow was low and constant, but performed poorly if streamflow was high and variable. In particular, the models are not capable of accurately simulating the effects of increasing stream width and bank storage due to rapid increases in streamflow. To better account for these effects a new analytical modeling framework is introduced which accounts for all major factors contributing to streamflow loss for a given site for both periods of pumping and periods between pumping. For the reach analyzed herein, the method illustrates that pumping wells often only caused half of the given streamflow loss occurring along the reach. This method can be used in other stream-aquifer systems impacted by nearby pumping. The U.S. Geological Survey's three-dimensional finite-difference groundwater flow model, MODFLOW, was also used to assess the impacts of pumping on streamflow. While MODFLOW removes many of the restrictive assumptions that define analytical solutions, certain limitations persist when the program is applied on local, fine scales with dynamic interactions between a stream and alluvium. In particular, when the average stream width is greater than the computational grid cell size, the model will return systematically biased, grid-dependent results. Moreover, simulated streamflow loss will be limited in the range of values that can be modeled. To address these limitations, a new stream module is presented which (1) allows for streams to dynamically span multiple computational grid cells over a cross section to allow for a finer mesh; (2) computes streamflow and backwater stage along a stream reach using the quasi-steady dynamic wave approximation to the St. Venant equations, which allows for more accurate stream stages when normal flow cannot be assumed or a rating curve is not available; and (3) incorporates a process for computing streamflow loss when an unsaturated zone develops under the streambed. Streamflow loss is not assumed constant along a cross section. It is shown that most streamflow loss occurs along stream banks and over newly inundated areas after increases in upstream streamflow. The new module is tested against streamflow and groundwater data collected in a stream-aquifer system along the South Platte River in Denver, Colorado and to estimate the impact of nearby pumping wells on streamflow. When compared with existing stream modules more accurate results are obtained from the new module. The new module can be applied to other small-scale stream-aquifer systems.
Keywords: groundwater; MODFLOW; streamflow depletion; hyporheic zone; analytical modeling; numerical modeling